Tanggung Jawab Notaris Terhadap Keabsahan Identitas Penghadap Dalam Pembuatan Akta Pengakuan Hutang Dan Kuasa Jual - Aditya Salsabila Consoleo; Sulasno Sulasno; Rokilah Rokilah (Faculty of Social, Politic, and Law Science, Universitas Serang Raya, 2023)
If the notary is not careful, he or she will face problems where the data is false or erroneous, as was the case in this study where the party who wanted to make an agreement did not provide actual information that their marital status was legally valid. This will have detrimental implications for one of the parties in the event of a divorce, because the assets acquired during the marriage period are joint property and should be joint property. This research aims to find out 1). To find out the responsibility of the notary regarding the validity of the identity of the applicant in making the deed of acknowledgment of debt and power of sale, 2). To find out the legal consequences that will arise from the notary's negligence in examining the applicant's data when making the deed. This research uses a qualitative method with a normative juridical research type using secondary data as the main data and using a statutory approach. The results of this research show that: 1). Notary Civil Liability, Notary Criminal Liability, Notary Administrative Liability and Notary Code of Ethics Accountability 2). If the notary is negligent, whether intentionally or unintentionally, the Notary is obliged to be responsible for his actions regarding the deed, so that if there is proven false identity.